Ethical Implications of the Fecal Microbiota Transplantation: Disclosure of a False-Positive HIV Test - Caitlyn Hollingshead; Jacob Ciricillo; Joel Kammeyer (Case Reports in Infectious Diseases)
Fecal microbiota transplantation (FMT) has gained popularity as an effective therapeutic option for Clostridioides difficile infection (CDI). Since its FDA recognition as a treatment modality for recurrent CDI in 2013, screening protocols for FMT donor stool have been in flux. However, extensive health questionnaires, in combination with serological and stool assays, have become mainstays in the donor screening process, although ethical implications are yet to be thoroughly considered. Herein, we present the case of a family member found to have a false-positive HIV test during the donor screening process and discuss potential ethical ramifications associated with FMT stool donation.